Electrophysiologic study of spraymen exposed to insecticide Lambda-cyhalothrin - Arunodaya, G R; Kumar, K R; Swamy, H S; Murugendrappa, M V (Neurology India, 1997)
Lambda-cyhalothrin ia a potent insecticide which acts by producing prolonging the duration of opening of sodium channels in neurons. While it is being used in several countries, no extensive neurophysiologic study of toxic effects in humans is available. We performed multimodality electro-physiologic studies in 15 spraymen in the age range of 19-48 years, before and after the exposure to this insecticide, with a view to detect any neurotoxic manifestation. Facial nerve conduction, blink response, repetitive stimulation test and visual, auditory and somatosensory evoked potentials were normal. Six subjects had mild changes in peripheral nerve conduction parameters. Comparison of mean values of the various nerve conduction studies in three subjects showed normal findings. We conclude that Lambda-cyhalothrin may produce transient, subclinical, electrophysiologic changes in the nerves of upper limb, possibly as a local toxic manifestation.